What Is the Ability Emotional Intelligence Test (MSCEIT) Good for? An Evaluation Using Item Response Theory - Fiori, Marina (Public Library of Science, 2014)
The ability approach has been indicated as promising for advancing research in emotional intelligence (EI). However, there is scarcity of tests measuring EI as a form of intelligence. The Mayer Salovey Caruso Emotional Intelligence Test, or MSCEIT, is among the few available and the most widespread measure of EI as an ability. This implies that conclusions about the value of EI as a meaningful construct and about its utility in predicting various outcomes mainly rely on the properties of this test. We tested whether individuals who have the highest probability of choosing the most correct response on any item of the test are also those who have the strongest EI ability. Results showed that this is not the case for most items: The answer indicated by experts as the most correct in several cases was not associated with the highest ability; furthermore, items appeared too easy to challenge individuals high in EI. Overall results suggest that the MSCEIT is best suited to discriminate persons at the low end of the trait. Results are discussed in light of applied and theoretical considerations.